2008
DOI: 10.3758/pbr.15.2.372
|View full text |Cite
|
Sign up to set email alerts
|

Were you paying attention to where you looked? The role of executive working memory in visual search

Abstract: Recent evidence has indicated that performing a working memory task that loads executive working memory leads to less efficient visual search (Han & Kim, 2004). We explored the role that executive functioning plays in visual search by examining the pattern of eye movements while participants performed a search task with or without a secondary executive working memory task. Results indicate that executive functioning plays two roles in visual search: the identification of objects and the control of the disengag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
25
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 26 publications
7
25
1
Order By: Relevance
“…From the analyses of fixation locations, we know that many dots were revisited. Although these results suggest that the eyes do not have a perfect memory, it is possible that they have some memory for previous fixations (Beck et al, 2006;Peterson et al, 2008;Peterson et al, 2001). To examine this possibility, we compared the observed proportion of nonimmediate refixations with that predicted by a nomemory model.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…From the analyses of fixation locations, we know that many dots were revisited. Although these results suggest that the eyes do not have a perfect memory, it is possible that they have some memory for previous fixations (Beck et al, 2006;Peterson et al, 2008;Peterson et al, 2001). To examine this possibility, we compared the observed proportion of nonimmediate refixations with that predicted by a nomemory model.…”
Section: Resultsmentioning
confidence: 99%
“…When interpreting the difference in intercepts of RT in Experiment 1, we suggested an interpretation in terms of subitizing: Subjects index fewer dots in the count condithe proportion of refixation and reduce search efficiency (Han & Kim, 2004;Peterson et al, 2008). Peterson et al (2008) suggested that attention may move away from one item before processing is completed, so a refixation is necessary to complete processing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations